A Unique Case of Autoimmune Retinopathy Associated with Anti-Alpha-Enolase Antibodies - Paul A. Kurz; Rachel E. Reem; Daryl E. Kurz; Richard G. Weleber (Case Reports in Ophthalmological Medicine)
Background. We report a case of autoimmune retinopathy associated with anti-alpha-enolase antibodies with unique manifestations. Methods. A case report. Results. A 30-year-old male experienced recurrent, primarily peripheral visual field disturbances and minimal photopsia, with interval symptom resolution. Fundus changes subsequently developed in areas corresponding to the previous visual field symptoms. Electroretinogram showed bilaterally symmetric abnormalities of light-adapted responses and suggested loss of photoreceptor function. Only anti-alpha-enolase antibodies were detected on Western blot. Our patient noted cutaneous symptoms at the time of both episodes of visual symptoms, but not in the interim. Biomicroscopy revealed subtle small reddish spots in areas of the peripheral retina corresponding to the areas of the patient’s visual field where he noted symptoms. To our knowledge these reddish spots have not been reported in autoimmune retinopathy and may clinically support in vitro and in vivo evidence that anti-alpha-enolase antibodies may target photoreceptors. Conclusions. Our patient demonstrates some unique features adding to the known characteristics of autoimmune retinopathy associated with anti-alpha-enolase antibodies. As more cases are reported, further understanding of the features and pathophysiology of this rare condition will hopefully be elucidated.